Pendidikan Kepribadian Anak Menurut Abdullah Nashih Ulwan - Ali Imron (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2016)
Children are great imitators who always imitate people around them. As they are precious gifts from God, it is an obligation to look after and educate them in a proper manner with Islamic values such as giving behavior education to the children. Abdullah Nashih Ulwan said that behavior education is very important for children. Educators, including parents and society, are responsible for developing it. The behavior education which should be developed includes three domains; they are physical education, intellectual education, and spiritual education as well.